Anatomy and physicochemical properties of the chambira fiber - Marín, Manuel (2012)
The anatomy of the unopened spear leaf of the chambira palm (Astrocaryum chambira), from which chambira fiber is extracted, is described and compared with that of three species (Astrocaryum jauari, occasionally used for fiber extraction, A. standleyanum and A. perangustatum, which do not provide any fiber). Chambira fiber consists of non-vascular fiber strands closely adhered to the adaxial hypodermis; this forms a compact unit, which makes it easy to separate from the rest of the lamina. A similar arrangement is found in Astrocaryum jauari; however, the non-vascular fiber cells are shorter and fewer per strand. Differences in leaf anatomy of Astrocaryum standleyanum and A. perangustatum may explain why fiber is not extracted: Astrocaryum standleyanum has a dense row of non-vascular fibrous strands under the adaxial hypodermis similar to Astrocaryum chambira but the large size of non-vascular fibrous strands that are located in the abaxial part of the mesophyll makes it difficult to properly extract fiber as is done with chambira. In Astrocaryum perangustatum, non-vascular fiber strands are small and irregularly dispersed in the mesophyll, which makes it impossible to extract quality fibers. Density, thickness and tensile strength are higher in chambira fiber than in jauari fiber. Chambira fiber presents a very high cellulose content (93.9%), while lignin content is low (4.2%). The ultrastructure of the cell wall of the non-vascular fiber is described for Astrocaryum chambira only. The major trait is a three-layered cell wall, with a notably thick inner layer. The physicochemical properties of chambira fiber are compared with other vegetal fibers used by the industry.